Anestezjologia i intensywna terapiaSelection of agents for postoperative sedation of patients after cardiac surgery. Will alpha2-adrenoceptor agonists meet our expectations? - Borkowski, Jarosław; Knapik, Piotr; Krzemiński, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Very few patients with a low operative risk are nowadays referred to the cardiac surgeon, therefore any drugs used in this specific popu-lation should be absolutely safe. Adequate sedation in the early postoperative period after cardiac surgery is essential as it provides both stability of the circulatory system and protection against ischemia. Various drugs may be used to provide perioperative sedation. Opioid analgesics, sedatives and anaesthetics are most commonly used. Most recently, α2 adrenoreceptor agonists, very popular in the perioperative medicine, have also been proposed for sedation. Dexmedetomidine is the newest highly selective α2 adrenoreceptor agonist with sedative, sympatholitic and analgesic properties. Dexmedetomidine has been confirmed to be a safe sedative agent in many studies, however some serious adverse events have also been described. This issue should be extensively studied and deserves further investigation.